Seabirds (IntechOpen, 2023)
Changes in seabird populations are good indicators of large-scale and long-term change in marine ecosystems, and are important because of their global impacts on the marine environment. This book has six chapters that present a wide variety of global seabird-related issues, from India to Svalbard, Norway. It also gives a comprehensive history of the use and chemical content of guano and certification schemes in fisheries for seabird conservation in Argentina. With the knowledge available in this book we should know how best to protect seabirds, which need all our support to survive in changing environments and climates. We can all do our best to recycle plastic waste to reduce global plastic pollution, which has affected seabirds' physical state, food sources, and nesting areas.